2021
DOI: 10.1029/2021gl093416
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial Organic Carbon Composition Regulated by Seasonal Variability in Lowland River Migration and Water Discharge

Abstract: Burial of particulate organic carbon (POC) in sedimentary basins drives a long-term atmospheric CO 2 sink (e.g., France-Lanord & Derry, 1997) and creates paleoclimate archives (e.g., Hein et al., 2017). However, POC flux to depositional basins, and the paleoclimate conditions recorded therein, can be modulated during source to sink transit, analogous to how fluvial transport modifies environmental signals in clastic deposits (Hajek & Straub, 2017;Jerolmack & Paola, 2010). In lowland rivers, sediment exchange b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Flood conditions may also increase sediment transport capacity and accelerate bank erosion, increasing fluxes of discrete POC. During low-flow conditions, coarse discrete POC is more likely to be deposited and oxidized on braid and point bars due to reduced transport capacity, resulting in predominant export of mineral-associated organic matter from the headwaters (e.g., Golombek et al, 2021). Furthermore, in the Rio Bermejo we observed water-logged plant debris traveling in an undercurrent near the river bed, similar to observations in the Madre de Dios River (Feng et al, 2016).…”
Section: Hydrodynamic Sorting Effects On Fluvial Poc Fluxessupporting
confidence: 76%
See 2 more Smart Citations
“…Flood conditions may also increase sediment transport capacity and accelerate bank erosion, increasing fluxes of discrete POC. During low-flow conditions, coarse discrete POC is more likely to be deposited and oxidized on braid and point bars due to reduced transport capacity, resulting in predominant export of mineral-associated organic matter from the headwaters (e.g., Golombek et al, 2021). Furthermore, in the Rio Bermejo we observed water-logged plant debris traveling in an undercurrent near the river bed, similar to observations in the Madre de Dios River (Feng et al, 2016).…”
Section: Hydrodynamic Sorting Effects On Fluvial Poc Fluxessupporting
confidence: 76%
“…We found that total Q POC , primarily Q POC, f , increased significantly between downstream km 135 and 420, coincident with an increase in lateral channel migration rate. These results highlight river bank erosion as a key mechanism for delivering mineral‐associated POC to downstream sedimentary basins (Galy et al., 2015; Golombek et al., 2021; Torres et al., 2017), where it can be buried and preserved, contributing to long‐term CO 2 drawdown (Barber et al., 2017; Keil, Tsamakis, et al., 1994; Mead & Goñi, 2008).…”
Section: Hydrodynamic Sorting Effects On Fluvial Poc Fluxesmentioning
confidence: 91%
See 1 more Smart Citation
“…To conclude, multiple flooding events can comprise different proportions of sediment sources and transport processes. This temporal variability applies not only to the inter‐seasonal variation as previously observed (Golombek et al., 2021; Jian et al., 2020) but also to the variations within a single season. The temporal variation observed in this case study poses constraints on the interpretation of compositional differences in terms of sediment provenance, and should be considered in studies of modern drainage basins as well as ancient sediment routing systems.…”
Section: Discussionsupporting
confidence: 61%
“…For rivers in the loess area more than 80% of the total suspended sediment can be ascribed to bank erosion and collapse (Simon et al., 2000). In addition, the transit of bank‐derived sediment from a given catchment to the ocean contributes to the global carbon cycle (Galy et al., 2015; Golombek et al., 2021; Repasch et al., 2022). For instance, lateral erosion of rivers cutting through floodplains releases additional organic carbon fluxes to downstream depositional sinks (e.g., tidal flats and deltas).…”
Section: Feedbacks Between Bank Retreat and Morphodynamicsmentioning
confidence: 99%